Lemongrass Extract Alleviates Oxidative Stress and Delayed the Loss of Climbing Ability in Transgenic Drosophila Model of Parkinson’s Disease - Siddique, Yasir H.; Naz, Falaq; Mantasha, I.; Shahid, M. (Letters in Drug Design & Discovery, 2021)
Background: Parkinson’s Disease (PD) is characterized by the aggregation of α- synuclein, formation of Lewy bodies and the selective loss of dopaminergic neurons of mesencephalic substantia nigra pars compacta (SNC) with the debilitating motor symptoms. Introduction: The available treatment for PD provides symptomatic relief with no control over the progression of the disease. The treatment is also associated with several side effects. As neurodegeneration in PD is also associated with oxidative stress, antioxidants from plants could play an important role in reducing PD symptoms. With this aim, we decided to study the effect of Lemongrass extract (LGE) on the transgenic Drosophila model of PD expressing human alpha synuclein in the neurons. Methods: The PD flies were allowed to feed on different doses of LGE established in diet for 24 days and then assayed for climbing ability and oxidative stress markers. The molecular docking study was also performed for citral (the component of the extract) and human α-synuclein. Results and discussion: A dose dependent significant improvement in the climbing ability and reduction in oxidative stress was observed in the PD flies exposed to LGE. In our earlier study on LGE, citral was found to be the main component of the extract by GC-MS analysis. The docking results also support the positive interaction between citral and human α-synuclein. Conclusion: The results suggest that LGE is potent in reducing the PD symptoms being mimicked in transgenic Drosophila.
Keywords: Drosophila